Sociodemographic factors associated with acceptance of COVID-19 vaccine and clinical trials in Uganda: a cross-sectional study in western Uganda - Isaac, Echoru; Patricia, Decanar Ajambo; Emmanuel, Keirania; Edmund E. M, Bukenya (BMC Public Health, 2021)
Background: Health experts agree that widespread use of safe and effective vaccines will rapidly contain the COVID-19 pandemic. The big question is whether these vaccines can easily be accepted by their end-users. Our study aimed at determining sociodemographic factors associated with acceptance of vaccines and clinical trials of COVID-19 in western Uganda. Method: A simplified snowball sampling technique was used to select 1067 respondents of 18–70 years in western Uganda using an online questionnaire from July to September 2020. Vaccine acceptability and risk perception were assessed using odds ratio at 95% confidence interval in R software version 3.6.3. Results: There were 1067 participants in the study. The majority were males (73.2%) and age group 31– 40 years (32.6%). The acceptance rate for COVID-19 vaccination was (53.6%; 572/1067) with those aged 18–20 years, males, elites at tertiary level of education (degree or diploma), students, Muslims, married, non-salary earners and rural dwellers having better odds and likeliness to accept vaccination. Only 44.6% (476/1067) showed interest in clinical trials among which; males, primary school leavers, students, Christians, un-married, respondents who didn’t earn any salary and rural dwellers had better odds and likelihood to participate in clinical trials. Conclusion: There was a low level of vaccine acceptance and clinical trial interest in western Uganda. Minority groups in the study i.e., Muslims, students, primary school leavers, un-married rural dwellers among others showed more interest in vaccination and clinical trials. We anticipated fears in the larger part of this community that health experts need to address through reassurance of the community that vaccines are tested and that they are safe and important if we are to rapidly contain the COVID-19 pandemic.